Genetic and Epigenetic Causes of Pituitary Adenomas - Chang, Mengqi; Yang, Chengxian; Bao, Xinjie; Wang, Renzhi (Frontiers in Endocrinology, 2021)
Substantial advances have been made in the pathobiology of pituitary adenomas. Based on the blood hormone content of patients, pituitary tumors are classified as nonsecreting adenoma, growth hormone-secreting adenoma, corticotrophin-secreting adenoma, prolactin-secreting adenoma or thyrotropin-secreting adenoma. To obtain an accurate and comprehensive understanding of the molecular biological characteristics of different types of pituitary adenomas, we summarized the substantial advances involved mutations and epigenetic variations in different types of pituitary adenoma, and the application of molecular-targeted drugs is described. Growth hormone-secreting adenomas involve mutations of AIP, CDKN1B, GNAS, GPR101, CDH23 and IGSF1 and exhibit hypermethylation of GADD45γ, RB1, SSTR5 and GH1, while altered microRNAs target PTEN, HMGA2 and E2F1. Corticotrophin adenomas exhibit mutations in USP8, USP48, BRAF, MLH1 and MSH2 and hypermethylation of the POMC, ESR1, PTAG, FGFR2 and CAPS8 genes, while microRNAs that target SOX5 are regulated. Non-secreting adenomas exhibit mutations in MEN1, PIK3CA, CDH23 and AIP, abnormal methylation levels of CDKN2A, FAM90A1, ING2 and GADD45 and microRNA regulation. Prolactin adenomas exhibit mutations of AIP, MEN1, CDKN2A, HMGA2 and PRLR. We summarize potential invasive markers including MMP family proteins and FGFR proteins and novel markers including LAMA2, WIF1 and lncRNA-H19. In this review, we summarized the genetic and epigenetic background of pituitary adenomas, focusing on recent developments in this field.